Mechanical vulnerability and resistance to snapping and uprooting for Central Amazon tree species - Ribeiro, Gabriel Henrique Pires de Mello; Chambers, Jeffrey Quintin; J, Peterson, Chris; Trumbore, Susan Elizabeth; Marra, Daniel Magnabosco; Wirth, Christian B.; B, Cannon, Jeffery; Negrón-Juárez, Robinson I.; Lima, Adriano José Nogueira; Paula, E. V.C.M. de; Santos, Joaquim dos; Higuchi, Niro (Forest Ecology and Management, 2016)
High descending winds generated by convective storms are a frequent and a major source of tree mortality disturbance events in the Amazon, affecting forest structure and diversity across a variety of scales, and more frequently observed in western and central portions of the basin. Soil texture in the Central Amazon also varies significantly with elevation along a topographic gradient, with decreasing clay content on plateaus, slopes and valleys respectively. In this study we investigated the critical turning moments (Mcrit - rotational force at the moment of tree failure, an indicator of tree stability or wind resistance) of 60 trees, ranging from 19.0 to 41.1 cm in diameter at breast height (DBH) and located in different topographic positions, and for different species, using a cable-winch load-cell system. Our approach used torque as a measure of tree failure to the point of snapping or uprooting. This approach provides a better understanding of the mechanical forces required to topple trees in tropical forests, and will inform models of wind throw disturbance. Across the topographic positions, size controlled variation in Mcrit was quantified for cardeiro (Scleronema mincranthum (Ducke) Ducke), mata-matá (Eschweilera spp.), and a random selection of trees from 19 other species. Our analysis of Mcrit revealed that tree resistance to failure increased with size (DBH and ABG) and differed among species. No effects of topography or failure mode were found for the species either separately or pooled. For the random species, total variance in Mcrit explained by tree size metrics increased from an R2 of 0.49 for DBH alone, to 0.68 when both DBH and stem fresh wood density (SWD) were included in a multiple regression model. This mechanistic approach allows the comparison of tree vulnerability induced by wind damage across ecosystems, and facilitates the use of forest structural information in ecosystem models that include variable resistance of trees to mortality inducing factors. Our results indicate that observed topographic differences in windthrow vulnerability are likely due to elevational differences in wind velocities, rather than by differences in soil-related factors that might effect Mcrit. © 2016
Keywords: Biology; Ecology; Ecosystems; Regression Analysis; Blow Down; Functional Traits; Tree Allometry; Tree Static Winching; Turning Moment; Wind Disturbance; Forestry; Allometry; Disturbance; Ecological Modeling; Ecosystem Structure; Forest Ecosystem; Mortality; Soil Texture; Species Diversity; Tree; Tropical Forest; Vulnerability; Wind Velocity; Windthrow; Woody Plant; Amazonia; Eschweilera; Scleronema